(untitled) (Research, Society and Development, 2022)
The Composition discipline and the Composition Course assume an important role in the curriculum of the specialized artistic teaching of music, in Portugal, which manifests itself since the creation of the Lisbon Conservatory, linked to Casa Pia (1835), until today. This article describes a chapter of the PhD in Artistic Education - Music Education of the PhD Program in Child Studies of the University of Minho and has as main objective to make a study of the historical evolution of the Composition Course and its analogous disciplines, within the specialized artistic teaching of music, through a chronological analysis of the different curricular reforms occurred since the foundation of the Conservatory of Lisbon, until the last reform occurred with the Decree-Law No. 310/83, of July 1, and the subsequent restructuring that remains to this day. As a specific objective, it is intended to situate the current state of the art in which the Composition discipline and the Composition Course are found in the specialized music schools in Portugal. The methodology adopted has privileged the analysis of the content of the legislation published for the teaching of music, as well as other documentation considered pertinent to substantiate the work.